KONTRIBUSI PERSEPSI SISWA TENTANG KETERAMPILAN MENGAJAR GURU DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MENERAPKAN DASAR-DASAR ELEKTRONIKA DI SMK NEGERI 1 BATIPUH - Dian Permatasari; Nelda Azhar; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
The problem in this research is the low value of the subjects implementing the basics of electronics X Mechanical Audio Video SMK Negeri 1 Batipuh. Minimum completeness criteria (KKM) assigned to the lesson applies the basics of electronics students of Class X Mechanical Audio Video SMK Negeri 1 Batipuh was 7.22 with a range of values (0-10). The fact that 69.23% students get to apply the basics of electronics of <7.22 and 30.77% of students gained grades ≥ 7.22 in the academic year 2015/2016.The purpose of this study to reveal how much the contribution Perceptions of students on Teachers Teaching Skills and Motivation to Apply Learning Outcomes subjects Fundamentals of Electronics at SMK Negeri 1 Batipuh. The study population numbered 52 people and a sample of 35 students of class X Audio Video Engineering department at SMK Negeri 1 Batipuh. Data perceptions of students about teachers' teaching skills and learning motivation were collected through a questionnaire distributed to students of class X Audio Video Engineering program membership in SMK Negeri 1 Batipuh using a Likert scale that has been tested for validity and reliability. While the data is the result of class X student majoring in Engineering Audio Video obtained from the Administrative SMK Negeri 1 Batipuh.The results of data analysis showed that that (1) Perceptions of students On Skills Teachers and motivation to learn together make a significant contribution of 45.21% to the learning outcomes Applying Fundamentals of Electronics at SMK Negeri 1 Batipuh (2) Student Perceptions About Teaching skills Teachers make a significant contribution of 15.60% to the learning outcomes Applying Fundamentals of Electronics at SMK Negeri 1 Batipuh (3) learning motivation contribute significantly by 12.57% to the learning outcomes Applying Bases in SMK Electronics 1 Batipuh. So it can be concluded that the perception of students On Skills Teachers and motivation to learn together and partially berkontriusi the Learning Results subjects Applying Fundamentals of Electronics student at SMK 1 Batipuh, the more positive the Student Perceptions About Skills Teachers and the better Motivation, then increasing learning results obtained by the students. Keywords: Student Perceptions of Teaching Teachers About Skills, Motivation, Learning Outcomes.